Sistem Pertanian Terpadu di Lahan Kering : Integrasi Sapi-Jagung-Gamal di Das Batu Lanteh, Sumbawa - Sudarli Sudarli; Muhammad Sarjan; Arifuddin Sahidu; Amrullah Amrullah; Ahmadi Ahmadi; Husnul Jannah; Mutia Devi Ariyana; Gunawan Gunawan; Aida Muspiah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The Integrated Agricultural System (SPT) is a strategic approach in dryland development, as it is able to respond to various biophysical constraints such as water limitations, low soil fertility, and production fluctuations. In the Batu Lanteh watershed, Sumbawa Regency, the integration of cattle-corn-gamal is a synergistic model that combines the production of food crops, the provision of forage feed, and the use of livestock waste as a source of organic fertilizer. Various studies show that plant-livestock-tree integration can increase corn productivity, improve soil quality, increase land use efficiency, and strengthen the economic resilience of farmer households (Irawan et al., 2024; Panjaitan et al., 2019). This study analyzes the integration system from an epistemological perspective, especially in looking at the relationship between farmers' local knowledge and scientific knowledge developed through research and program interventions. The results of the review show that there is an epistemological tension between local knowledge that is empirical-contextual and scientific knowledge that is procedural-generalizing. However, the integration of the two is possible through a hybrid epistemology that emphasizes co-creation of knowledge, dual validation, and farmer participation in the innovation process. The conclusion of the study emphasizes that the success of cattle-corn-gamal integration is largely determined by the harmonization between local and scientific perspectives, so that this epistemological approach becomes the basis for the formulation of a more adaptive, participatory, and sustainable dryland agricultural policy in Sumbawa Regency.